2022
DOI: 10.3390/ijerph20010473
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Maternal Education and Child Nutrition and Oral Health in an Indigenous Population in Ecuador

Abstract: The global nutrition transition has increased the prevalence of childhood dental caries. Greater understanding is needed of the impact of social determinants—including maternal education—on child oral health. This is a cross-sectional analysis of a convenience sample of families of 458 indigenous Ecuadorian children aged 6 months through 6 years from 2011–2013. Data was collected by mother interviews and child dental and anthropometric examinations. Multivariate logistic and Zero-Inflated-Poisson regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
0
0
1
Order By: Relevance
“…Переважно, зниження рівня стоматологічного здоров'я відзначають в сільській місцевості та серед корінного населення країни -до 95,0% таких 6-річних дітей зазначених вражені карієсом зубів. Тому ряд публікацій вказують на вплив соціальних та економічних факторів та умов на розвиток карієсу зубів у дітей та акцентують увагу на важливості мультидисциплінарного та локалізованого до рівня громад принципу побудови програм стоматологічної профілактики, оскільки взаємодія лише з дітьми та матерями (освітні та санітарно-просвітницькі заходи) не призводять до суттєвого ефекту [46][47][48][49].…”
Section: нерівномірна ефективність профілактичних заходів -нерівність...unclassified
“…Переважно, зниження рівня стоматологічного здоров'я відзначають в сільській місцевості та серед корінного населення країни -до 95,0% таких 6-річних дітей зазначених вражені карієсом зубів. Тому ряд публікацій вказують на вплив соціальних та економічних факторів та умов на розвиток карієсу зубів у дітей та акцентують увагу на важливості мультидисциплінарного та локалізованого до рівня громад принципу побудови програм стоматологічної профілактики, оскільки взаємодія лише з дітьми та матерями (освітні та санітарно-просвітницькі заходи) не призводять до суттєвого ефекту [46][47][48][49].…”
Section: нерівномірна ефективність профілактичних заходів -нерівність...unclassified
“…Furthermore, pregnant women should indulge in their cravings, although many involve sugary foods [15,18]. Specific authors suggest a direct connection between these beliefs and poor oral health during pregnancy [19,20]. Other authors suggest that being Indigenous may be associated with poor oral health [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors suggest that being Indigenous may be associated with poor oral health [18,21]. However, other studies have not found such an association [20,22]. Lower attendance at the dental office during pregnancy was also described [3,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding oral diseases, dental caries in children has shown high levels of prevalence and experience [24,25]. Although studies focusing specifically on preschool-aged children are limited in the country, a strong association has been found between low maternal education and a higher prevalence and severity of dental caries in children from rural indigenous communities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%